Development of Teaching Modules in Problem-Based Mathematics Learning to Improve Junior High School Students' Mathematical Literacy - Cahyani, Rezzah Indach; Iskandar, Ratu Sarah Fauziah; Sukmawati, Rika; Raza, Ali (EDUPEDIA Publisher, 2024)
Based on the observations and interviews at State Junior High School 8 Tangerang, data was obtained from the teaching modules at the school. Explaining the material in the teaching module has not improved students' mathematical literacy skills. The aim of this research is: (1) to develop a teaching module as a learning module on social arithmetic material for class 7 of State Junior High School 8 Tangerang, (2) to determine the feasibility of the teaching module, (3) find out the assessment of class seventh students at state junior high school 8 Tangerang regarding the development of teaching modules. This research is a development research or Research and Development (R&D) type. The steps in this research are potential and problems, collecting information, product design, product validation, product improvement, and product testing. The instrument used in this research was a learning media validation sheet. Based on the validation results by media and material experts, the average was 4.50 out of a maximum score of 5.00, and learning practitioners averaged 4.57 out of a maximum score of 5.00, categorized as very feasible. The results of the teaching module trial received a very good response from students, with an average of 3.88 out of a score of 4.00, meaning that the teaching module was very suitable for use in the learning module.